Probabilistic assessment of extreme temperature dynamics - Šeputytė, Ilona; Alzbutas, Robertas (Lietuvos matematikos rinkinys, 2015)
In order to estimate likelihood of the annual minimum and maximum Lithuanian air temperatures (based on 1961–2014 data) the probabilistic assessment using the extreme value distributions was performed, in particular, for each sample the best extreme value distribution was identified. In addition, to the previously mentioned study of dry bulb temperature extremes, wet bulb temperature extremes study, which enables to determine the relative humidity, was also carried out. Usingthe selected Gumbel distribution, the local temperature data analysis in eastern Lithuania, i.e. in Dūkštas, region was conducted. Then temperature variation analysis using the moving average method was carried out and the extremes changes in view of the uncertain data were investigated.
Keywords: extreme temperature; dynamics; probabilistic assessment